2019
DOI: 10.3390/su11236739
|View full text |Cite
|
Sign up to set email alerts
|

“Take It or Leave It”: From Collaborative to Regulative Developer Dialogues in Six Swedish Municipalities Aiming to Climate-Proof Urban Planning

Abstract: Enhancing legitimacy and effectiveness of climate policy requires improved interactions between and within administrative levels, the latter including horizontal public–private coordination. In the heavily decentralized Swedish urban planning process, developer dialogues are used to enhance collaboration and thereby increase the climate-proofing of new housing districts. In practice, municipalities struggle with identifying what types of collaborative arrangements best support the realization of climate goals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However, the result shows that they believe property owners (S4) and companies (S14, S15) also need to take on responsibility for societal adaptation. This indicates that the result corresponds with the academic studies calling for a shared public-private responsibility [5,7,9]. These results reflect current Swedish legislation, placing responsibility on local governments and property owners, and also reflect the result of the public investigation from 2017, coming to the conclusion that property owners have an unreasonably large responsibility [40].…”
Section: Who Should Be Responsible For What?supporting
confidence: 78%
See 2 more Smart Citations
“…However, the result shows that they believe property owners (S4) and companies (S14, S15) also need to take on responsibility for societal adaptation. This indicates that the result corresponds with the academic studies calling for a shared public-private responsibility [5,7,9]. These results reflect current Swedish legislation, placing responsibility on local governments and property owners, and also reflect the result of the public investigation from 2017, coming to the conclusion that property owners have an unreasonably large responsibility [40].…”
Section: Who Should Be Responsible For What?supporting
confidence: 78%
“…37% reported total or nearly total agreement (levels 6 or 7), while only 13% reported that they totally or nearly totally disagreed. Almost half of the respondents (49%) ended up in one of the middle levels (3)(4)(5) or answered "don't know". Even within the mid-range, the distribution is fairly right-skewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the limited existing information about decision-making for centralized accommodations in emergency contexts, this study is a valuable contribution to the body of knowledge [69]. For instance, existing studies have validated that meaningful information can be drawn from small sample sets (e.g., [48][49][50]). Many patterns of decision-making and themes discussed in interviews were common regardless of the informants' backgrounds, but future research could assess how such backgrounds affect decision-making in a context such as the one studied here.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…A qualitative analysis of these interviews was used to identify trends and emergent themes in decision-making processes in a context about which existing information is scarce [46,47]. Similar methods of qualitative analysis of interviews were used in previous studies and were proven successful in identifying patterns in stakeholder perspectives (e.g., [48][49][50]; these studies used between seven and 15 semi-structured interviews). More specifically, qualitative coding was used to capture interviews' "primary content[s] and essence" [51] (page 4) and "retrieve and categorize data that are similar in meaning" [52].…”
Section: Methodsmentioning
confidence: 99%